2014
DOI: 10.1590/s1413-41522014000200004
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação dos resíduos de serviços de saúde do Grupo A em hospitais de Vitória (ES), Brasil

Abstract: Group A -biological risk; 1.5% Group B -chemical risk; and 0. 05% Group E -sharps.The apparent bulk density was 106.2 kg/m3. The average production rate of this mixture was 2. 68 kg per occupied bed daily. By separating the mixture of the RSS from group D, the average production rate of Group A changed to 1. 15 kg per occupied bed daily, reducing incineration costs by 58%. By segregating Groups B, D, E and subgroup A4, the average production rate changed to 0. 18 kg per occupied bed per day with a reduction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
2
12

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 3 publications
1
8
2
12
Order By: Relevance
“…In a study carried out in hospitals in the city of Vitória-ES, the average rate of production of non-sorting waste containing Group D waste mixed with Group A was 2.68 kg per bed occupied per day. The authors found that, by properly sorting the waste in their respective groups, the amount of Group A waste reduced from 2.68 to 1.15 kg per bed occupied per day, corresponding to a reduction of costs with Incineration of 57.71% (19) .…”
Section: Discussionmentioning
confidence: 99%
“…In a study carried out in hospitals in the city of Vitória-ES, the average rate of production of non-sorting waste containing Group D waste mixed with Group A was 2.68 kg per bed occupied per day. The authors found that, by properly sorting the waste in their respective groups, the amount of Group A waste reduced from 2.68 to 1.15 kg per bed occupied per day, corresponding to a reduction of costs with Incineration of 57.71% (19) .…”
Section: Discussionmentioning
confidence: 99%
“…Em complementação às apreciações documentais apresentadas, destacamos a seguir algumas observações obtidas nas visitas e entrevistas realizadas nos hospitais, em relação aos procedimentos praticados, sobretudo em termos de segregação e armazenamento externo dos RSS. Verificaram-se resíduos segregados em recipientes inapropriados, misturados e com diferentes classificações, o que também foi constatado em outros estudos (NÓBREGA; PIMENTEL; COSTA, 2008;OROZCO et al, 2011;ADUAN et al, 2014). Essa característica observada na segregação dos resíduos apresenta uma relação com a ausência de informações e a parcial suficiência de procedimentos especificados no item capacitação dos PGRSS analisados.…”
Section: • Trabalho De Campounclassified
“…Observa-se quão útil pode ser essa abordagem global na identificação de possíveis fragilidades de gestão em estabelecimentos específicos. Essa realidade de falha na segregação é presente em alguns hospitais brasileiros (ADUAN et al 2014;YAMANE;SIMAN, 2015) o que representa custo maior de destinação final, ou seja, maior dispêndio de recursos da saúde.…”
Section: Taxa De Produção De Rssunclassified